Vonoprazan-based triple and dual therapy versus bismuth-based quadruple therapy for Helicobacter pylori infection in China: a three-arm, randomised clinical trial protocol - ShaoWei Han; ZiJie Deng; KaShing Cheung; Tao Lyu; PuiLing Chan; Ying Li; Li Ni; XiaPeng Luo; Kuan Li (BMC Gastroenterology, 2023)
Abstract Background Helicobacter pylori infection and associated diseases are a growing global public health issue. H. pylori infection is the major cause of gastric cancer, over 90% of duodenal ulcers, and over 70% of gastric ulcers. The infection rate of H. pylori is approximately 50%, and approximately 50% of new cases of gastric cancer worldwide occur in China. Bismuth (BI)-based quadruple therapy is recommended as the first-line treatment for H. pylori in China. Vonoprazan (VPZ), a new potassium-competitive acid blocker that can inhibit gastric acid secretion more effectively than proton pump inhibitors (PPIs), has been combined with antibiotics to effectively eradicate H. pylori. In this study, we compared the efficacy and safety of two VPZ-based therapies with that of BI-based therapy for H. pylori treatment. Methods A three-armed randomised controlled trial (RCT) is being conducted in Shenzhen, with 327 participants recruited from the Gastroenterology Clinic of the University of Hong Kong-Shenzhen Hospital. Patients were diagnosed with H. pylori infection based on a positive 13C-urea breath test (UBT). Patients are kept naïve to their treatment and are randomly assigned in a 1:1:1 ratio to either VPZ-based triple, VPZ-based dual, or BI-based quadruple therapy for 14 days. All groups are subjected to follow-up evaluations of safety, adverse drug reactions, and clinical variables in the first, second, and fourth weeks after treatment. Successful eradication is confirmed by a negative 13C-UBT six weeks after treatment. If initial treatment fails, (1) those patients are turned to another regimen, or (2) a drug resistance test is conducted, after which an individualised treatment regimen shall be prescribed according to antimicrobial susceptibility testing. The resulting data will be evaluated using intention-treat and a per-protocol analysis. Discussion This study is the a RCT aims to evaluate the efficacy and safety of 14-day VPZ-based triple and dual therapies in comparison with BI-based quadruple therapy. The outcomes of this study may allow treatment recommendations and update drug instructions in China. Trial registration Chinese Clinical Trial Registry (No. ChiCTR2200056375). Registered on February 4, 2022, https://www.chictr.org.cn/showproj.aspx?proj=141314